Very rare presentation of perforated appendiceal adenocarcinoma within a prolapsed colostomy. Issue 12 (10th September 2020) - Alwatari, Yahya; Gardner, Graham; Fernandez, Leopoldo; Shah, Syed
Abstract: Appendiceal adenocarcinoma is rare with variable presentations. Perforation of the appendix within prolapsed ostomy can have peritoneal spread for which intraperitoneal chemotherapy should be considered. Surveillance is essential for these patients. Abstract : Appendiceal adenocarcinoma is rare with variable presentations. Perforation of the appendix within prolapsed ostomy can have peritoneal spread for which intraperitoneal chemotherapy should be considered. Surveillance is essential for these patients.